1996
DOI: 10.1070/rc1996v065n10abeh000278
|View full text |Cite
|
Sign up to set email alerts
|

Inner valence molecular orbitals and the structure of X-ray photoelectron spectra

Abstract: The effects of silver additive on the superconducting properties of YBa2Cu,,10,..,:Ag., for x = 0.1, 0.3, 0.6 and 1.2 are studied by measuring the real and imaginary components of the magnetic response in an AC field. The data are fitted to Bean's critical state model and are used to obtain the macroscopic critical current density. The magneticsusceptibilityand criticalcurrent density are found to dependon the silver content whereas T, remains essentially unchanged. For x = 1.2 the critical current density s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 41 publications
4
73
0
Order By: Relevance
“…Indeed, from the uncertainty relationship DEDt~h/2p (where DE is the half-width of the level from which an electron was removed, Dt is the lifetime of the hole, and h is Planck's constant) it follows that, if the O2s level were atomic, the half-width of the O2s line would be smaller than that of the O1s line, which is not the case. The mechanism of formation of the fine structure of the spectra of different elements including lanthanides in the range of binding energies from 0 to 50 eV was systematically studied in our previous work [13]. We found that inner valence MOs can be effectively formed in this range under certain conditions.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Indeed, from the uncertainty relationship DEDt~h/2p (where DE is the half-width of the level from which an electron was removed, Dt is the lifetime of the hole, and h is Planck's constant) it follows that, if the O2s level were atomic, the half-width of the O2s line would be smaller than that of the O1s line, which is not the case. The mechanism of formation of the fine structure of the spectra of different elements including lanthanides in the range of binding energies from 0 to 50 eV was systematically studied in our previous work [13]. We found that inner valence MOs can be effectively formed in this range under certain conditions.…”
Section: Resultsmentioning
confidence: 96%
“…Unfortunately, it is difficult to estimate quantitatively the relative intensity of this line and the number of weakly bound Fe3d electrons from the spectrum. The weak band at 12314 eV can be due to MO electrons of the carbonate anion CO 3 23 [13].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…15-50 eV) is usually well resolved and can be associated with the linear combinations of semicore AOs originating from closed (sub)shells. The latter, in contrast to valence AOs, in some cases can be combined to so-called internal MOs (IMOs) [11,12]. In the case of adsorption complexes, the formation of those IMOs can be monitored by the exaggerated binding energies of adatoms.…”
Section: Introductionmentioning
confidence: 99%